A model for active and healthy ageing with a rare genetic disease: cystic fibrosis. Issue 3 (March 2016) - Chiron, Raphael; Caimmi, Davide; Valiulis, Arunas; Durieu, Isabelle; Tejedor, Patrick; Le Cam, Yam; Boudes, Mathieu; Jonquet, Oliver; Strandberg, Timo; Michel, Jean-Pierre; de Manuel Keenoy, Esteban; Demoly, Pascal; et al.
Cystic fibrosis (CF), the most common life-limiting genetic condition in Caucasians, affects many organ systems. Specialised medical care, aggressive treatments [1] and proper nutrition both lengthen and improve quality of life for CF patients. Advances achieved over the last four decades have transformed CF from a fatal childhood disease to a long-term chronic condition. CF patients can now reach adulthood [2–5], although most of them still have a reduced life expectancy, and the adult population has passed from 44.55% in 2005 to 49.3% in 2010 (figure 1), the oldest patient being aged >80 years, from the 2010 European CF registry [6]. In the near future, even though CF paediatric care will remain crucial to assure the best growth for patients and transition to adulthood, CF centres may largely be considered as adult oriented [7], and we should, therefore, aim for the new concept of active and healthy ageing (AHA) in CF patients. Important controversies exist concerning the early- and long-term management of CF, which should be carefully considered when proposing a strategy for ageing well with CF [8]. Cystic fibrosis management today: an example of active and healthy ageing in patients suffering from a rare genetic disease http://ow.ly/V3JXt